1993
DOI: 10.1038/ng0693-143
|View full text |Cite
|
Sign up to set email alerts
|

The full mutation in the FMR–1 gene of male fragile X patients is absent in their sperm

Abstract: Fragile X syndrome is characterized at the molecular level by amplification of a (CGG)n repeat and hypermethylation of a CpG island preceeding the open reading frame of the fragile X gene (FMR-1) located in Xq27.3. Anticipation in this syndrome is associated with progressive amplification of the (CGG)n repeat from a premutation to a full mutation through consecutive generations. Remarkably, expansion of the premutation to the full mutation is strictly maternal. To clarify this parental influence we studied FMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
127
2

Year Published

1994
1994
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 238 publications
(135 citation statements)
references
References 42 publications
6
127
2
Order By: Relevance
“…21,22 Furthermore, although males with full mutations have full mutation alleles in their somatic cells, only premutation size alleles are present in sperm. 23 This is in stark contrast to full mutation expansions that occur, with increasing likelihood in female transmissions as allele size increases.…”
Section: Discussionmentioning
confidence: 91%
“…21,22 Furthermore, although males with full mutations have full mutation alleles in their somatic cells, only premutation size alleles are present in sperm. 23 This is in stark contrast to full mutation expansions that occur, with increasing likelihood in female transmissions as allele size increases.…”
Section: Discussionmentioning
confidence: 91%
“…In the fragile X syndrome, expansion of the trinucleotide repeat in the FMR1 gene from the premutation to the full mutation occurs exclusively when the mutation is inherited from the female (15). However, since the full mutation is absent from sperm of fragile X males, these expansions may be mitotic, occurring in the somatic cells of the affected offspring (16). Expansion of trinucleotide repeats in other disorders is also influenced by the sex of origin.…”
Section: Discussionmentioning
confidence: 99%
“…In 1993, Reyniers et al (33) showed the presence of a premutation and not a full mutation in sperm of patients with a full mutation in their blood cells. From this they postulated two hypotheses on the possible timing of the CGG repeat amplification.…”
Section: Discussionmentioning
confidence: 99%